The plant-like protein phosphatase PPKL regulates parasite replication and morphology in Toxoplasma gondii - Xi-Ting Wu; Xu-Wen Gao; Qiang-Qiang Wang; Kai He; Muhammad Saqib Bilal; Hui Dong; Yi-Dan Tang; Hui-Yong Ding; Yue-Bao Li; Xiao-Yan Tang; Shaojun Long (Parasites & Vectors, 2024)
Abstract Background The protozoan parasite Toxoplasma gondii encodes dozens of phosphatases, among which a plant-like phosphatase absent from mammalian genomes named PPKL, which is involved in regulating brassinosteroid signaling in Arabidopsis, was identified in the genome. Among the Apicomplexa parasites, T. gondii is an important and representative pathogen in humans and animals. PPKL was previously identified to modulate the apical integrity and morphology of the ookinetes and parasite motility and transmission in another important parasite, Plasmodium falciparum. However, the exact function of PPKL in the asexual stages of T. gondii remains unknown. Methods The plant auxin-inducible degron (AID) system was applied to dissect the phenotypes of PPKL in T. gondii. We first analyzed the phenotypes of the AID parasites at an induction time of 24 h, by staining of different organelles using their corresponding markers. These analyses were further conducted for the parasites grown in auxin for 6 and 12 h using a quantitative approach and for the type II strain ME49 of AID parasites. To further understand the phenotypes, the potential protein interactions were analyzed using a proximity biotin labeling approach. The essential role of PPKL in parasite replication was revealed. Results PPKL is localized in the apical region and nucleus and partially distributed in the cytoplasm of the parasite. The phenotyping of PPKL showed its essentiality for parasite replication and morphology. Further dissections demonstrate that PPKL is required for the maturation of daughter parasites in the mother cells, resulting in multiple nuclei in a single parasite. The phenotype of the daughter parasites and parasite morphology were observed in another type of T. gondii strain ME49. The substantial defect in parasite replication and morphology could be rescued by genetic complementation, thus supporting its essential function for PPKL in the formation of parasites. The protein interaction analysis showed the potential interaction of PPKL with diverse proteins, thus explaining the importance of PPKL in the parasite. Conclusions PPKL plays an important role in the formation of daughter parasites, revealing its subtle involvement in the proper maturation of the daughter parasites during division. Our detailed analysis also demonstrated that depletion of PPKL resulted in elongated tubulin fibers in the parasites. The important roles in the parasites are potentially attributed to the protein interaction mediated by kelch domains on the protein. Taken together, these findings contribute to our understanding of a key phosphatase involved in parasite replication, suggesting the potential of this phosphatase as a pharmaceutic target. Graphical Abstract